SOAR Analysis in the Development of Mitraguna Berkah Financing at Bank Syariah Indonesia KCP Tasikmalaya HZ Mustofa - Nurkaromah (Universitas Siliwangi), Silvia Ripa; Yuliani (Universitas Siliwangi), Nadia (Universitas Muhammadiyah Lampung, 2025)
This study aims to analyse the development strategy of Mitraguna Berkah financing products at Bank Syariah Indonesia (BSI) KCP Tasikmalaya HZ Mustofa using the SOAR (Strengths, Opportunities, Aspirations, Results) approach. This research uses descriptive qualitative methods through interview techniques and field observations. The results of the analysis show that the strength of the product lies in the payroll autodebet scheme, competitive margins, no collateral, as well as the support of digitalisation and communicative consumer human resources. Development opportunities are wide open through the potential of payroll customers, Islamic financial literacy, and untapped market areas. The resulting strategy includes increasing Islamic financial literacy, promoting bundling as a form of financial hijrah, strengthening the customer-centric approach based on spiritual values, and expanding through strategic partnerships.